Validity of wearable technology to measure peak impact during high-intensity treadmill running - Wundersitz, D.; Gastin, P.; Richter, C.; Netto, K. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to identify the validity of an upper-body mounted accelerometer to measure peak acceleration during high-intensity treadmill running. A twelve camera motion analysis (MA) system was used as the criterion measure with markers placed on and close to the accelerometer. Ten peak impacts per participant were compared (n = 390). All accelerometer values were significantly different between the MA unit and T6 reflective marker`s acceleration data. Smoothing accelerometer data at 8 and 6 Hz provides an acceptable indirect measure of peak impact acceleration performed during high-intensity running. Consequently, smoothing algorithms should be incorporated into the commercially available software that the devices are supplied with.